Early Byzantine Officials in the Southwestern Taurica According to the Seals from Cherson and Its Environ - Nikolaу A. Alekseienko (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения, 2019)
Introduction. Written sources and epigraphic monuments reflecting the history of Early Byzantine Cherson keep a few isolated accounts of some representatives of a large imperial administrative apparatus, which certainly existed in the city from the late 5th to the 8th century (komes, bikarios, doux, and archon).